The effect of drought on the growth and development of oil palm - a review / Mohammad Azzam A. Haris - A. Haris, Mohammad Azzam (Faculty of Plantation and Agrotechnology, 2017)
Drought can caused water deficiency which can interrupt the growth and development of oil palm. The drought or water shortage can inhibit the growth and development of leaf, fruit and root. Oil palm needs an average rainfall of 150 mm/month, with dry periods not more than 2 to 3 months. The relative air humidity must be above 75% in the whole year. The average for a minimum annual rainfall about 1800 mm which is at optimal rate and can raise up to 2500 mm without give any effect . There are several factors that can causes drought which are low precipitation, dry season, El-Nino, erosion and human activities and climate changes. All this factors will give an effect on growth and development of oil palm. The water shortage or drought can lead to growth inhibition of leaf, fruit and root of oil palm. Short period of drought or temperatures below 18°C does not significantly affect vegetative growth but reduced yield .The drought can make reduce the production of oil palm by reduced oil palm fruit weight. Oil palm smallholder and estate can reduce the effect of drought by creating a pond and water tank reservoir is necessary for drought protection.